2016
DOI: 10.15740/has/ijas/12.1/51-55
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis for yield and its components in sunflower (Helianthus annuus L.)

Abstract: Five lines were crossed with 10 testers in L x T mating design to estimate the combining ability for seed yield in sunflower. Non-additive genetic variance played a predominant role in the inheritance of all the characters studied viz., days to 50 per cent flowering, days to maturity, plant height, head diameter, number of seeds per head, 100 seed weight, seed yield per plant, hull content, volume weight and oil content. The lines CMS-148 and CMS-607 and testers SVR-467, SVR-490 and SVR-491 can be considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…This is maybe due to the aggregation of favorable genes from different traits in these superior backcrosses. The genetic variability among bi-parental sunflower crosses is consistent with those reported by Shinde et al (2016), Abd EL-Satar et al (2017) and Lakshman et al (2019).…”
Section: Mean Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…This is maybe due to the aggregation of favorable genes from different traits in these superior backcrosses. The genetic variability among bi-parental sunflower crosses is consistent with those reported by Shinde et al (2016), Abd EL-Satar et al (2017) and Lakshman et al (2019).…”
Section: Mean Performancesupporting
confidence: 90%
“…Similarly, Azad et al (2016 concluded the predominance of the non-additive gene action in inheritance of all the studied traits except for days to maturity. Additionally, many of the yield-attributing traits in sunflower are under the influence of non-additive gene action as reported by Shinde et al (2016), Abd EL-Satar et al (2017, Lakshman et al (2019) and Ahmed et al (2019). Consequently, according to the previous authors, the improvement of these traits can be performed by using hybrid varieties.…”
Section: Introductionmentioning
confidence: 95%
“…Non-additive gene action was reported for volume weight and test weight (100 seed weight) in sunflower which were similar to earlier reports by Mohanasundaram et al (2010). Similarly, for yield per plant and oil content were also governed by non-additive gene action in sunflower which were in accordance with Reddy and Madhavilatha (2005), Parameshwarappa et al (2008), Dudhe et al (2011), Patil et al (2012, Jondhale et al (2014) and Shinde et al (2016).…”
Section: Gca and Sca Variances For Restorer Linessupporting
confidence: 82%
“…Whereas for days to 50 per cent flowering higher magnitude of GCA variance than SCA variance was observed indicating the presence of additive gene action for this character which is in accordance with Ortis et al (2005). For plant height and head diameter non additive gene action was reported by Manivannan et al (2005), Reddy and Madhavilatha (2005), Pavani et al (2006), Parameshwarappa et al (2008), Mohanasundaram et al (2010), Dudhe et al (2011) and Shinde et al(2016) in sunflower. With respect to days to maturity nonadditive gene action was earlier reported in sunflower by Reddy and Madhavilatha (2005), Pavani et al (2006), Mohanasundaram et al (2010) and Shinde et al (2016).…”
Section: Gca and Sca Variances For Restorer Linesmentioning
confidence: 87%
“…Line A-1 (0.31) exhibited significantly positive GCA effects for AYP, which is desirable. The tester A-7 (0.16) showed significantly positive GCA effects, a desirable trait for AYP (Shinde et al, 2016). Line A-6 (3.337) exhibited highly significant positive GCA effects, which is desirable for OC.…”
Section: Resultsmentioning
confidence: 99%